Better slice of the market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The Jamaican agriculture and livestock sector should soon be benefiting from a new Research Centre, and a Demonstration and Training Centre (DTC), set up to help farmers and marketers in the local sheep and goat industry which, according to the...